Effect of herbicides and fungicides application on fibre yield and nutrient uptake by jute (Corchorus olitorius), residual nutrient status and soil quality - MAJUMDAR, B; SAHA, A R; SARKAR, S; MAJI, B; MAHAPATRA, B S (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was conducted during 2005–08 on a Aangetic alluvium soil to find out the effect of 2 preemergence (trifluralin and fluchloralin), 1 post-emergence herbicide (quizalofop ethyl) and 3 fungicides (carbendazim, mancozeb and copper oxychloride) applied on jute (Chorchorus olitorius L.) for fibre yield, nutrient uptake, residual nutrient status and soil quality parameters. Treatments having 2 hand weeding and hand weeding in combination with fungicides, and trifluralin @ 0.75 kg a i/ha recorded significantly higher fibre yield (74.7–78.9%) over the control and other herbicides but were at par among themselves. The nitrogen and phosphorus uptake by jute (3 years pooled data) follows the same trend as that of fibre yield, while fungicides along with hand weeding recorded significantly higher K and Zn uptake over the herbicides, hand weeding and the control. The residual nutrient status of soil after 3 years of cultivation increased in all treatments as compared to initial status, while hand weeding and trifluralin @ 0.75 kg a i/ha recorded substantially higher values of nutrients over other herbicides and fungicides. The enzyme activities (dehydrogenase, urease, fluorescein diacetate hydrolyzing activity and acid and alkaline phosphatase) in soil reduced significantly after 7 days of herbicide and fungicide application, while treatments having unweeded control and hand weeding maintained the same status as compared to initial status. The microbial biomass carbon and basic soil respiration rate of the soil follow the same trend as that of enzyme activities during 3rd year. The enzyme activities, microbial biomass carbon and basic soil respiration rate content in herbicides and fungicides treated plots started recovering after 15 days of their application and recovered almost to the extent of respective initial level at harvest. Among the herbicides and fungicides, trifluralin 0.75 kg a i/ha was the safest regarding soil quality next to hand weeding with higher fibre yield and residual nutrient availability.